Prospective Epidemiological Research Studies in Iran (the PERSIAN Cohort Study): Rationale, Objectives, and Design - Poustchi, Hossein; Eghtesad, Sareh; Kamangar, Farin; Etemadi, Arash; Keshtkar, Abbas-Ali; Hekmatdoost, Azita; Mohammadi, Zahra; Mahmoudi, Zahra; Shayanrad, Amaneh; Roozafzai, Farzin; Sheikh, Mahdi; Jalaeikhoo, Alireza; et al. (American journal of epidemiology, 2018)
Noncommunicable diseases (NCDs) account for 76% of deaths in Iran, and this number is on the rise, in parallel with global rates. Many risk factors associated with NCDs are preventable; however, it is first necessary to conduct observational studies to identify relevant risk factors and the most appropriate approach to controlling them. Iran is a multiethnic country; therefore, in 2014 the Ministry of Health and Medical Education launched a nationwide cohort study-Prospective Epidemiological Research Studies in Iran (PERSIAN)-in order to identify the most prevalent NCDs among Iran's ethnic groups and to investigate effective methods of prevention. The PERSIAN study consists of 4 population-based cohorts; the adult component (the PERSIAN Cohort Study), described in this article, is a prospective cohort study including 180,000 persons aged 35-70 years from 18 distinct areas of Iran. Upon joining the cohort, participants respond to interviewer-administered questionnaires. Blood, urine, hair, and nail samples are collected and stored. To ensure consistency, centrally purchased equipment is sent to all sites, and the same team trains all personnel. Routine visits and quality assurance/control measures are taken to ensure protocol adherence. Participants are followed for 15 years postenrollment. The PERSIAN study is currently in the enrollment phase; cohort profiles will soon emerge.